Tourists’ perceptions of world heritage destinations: The case of Guimarães (Portugal) - Remoaldo, Paula C. (2014)
Guimara˜es is a UNESCO world heritage site, deemed as such in 2001 and hosted the 2012 European Capital of Culture. This paper examines the profile, destination image, and motivations of tourists’ visiting behaviors in Guimara˜es before the cultural event. Based on survey responses from 276 tourists, we found that tourists arriving in Guimara˜es had previously visited the two most important cities in the northern part of Portugal. These respondents were relatively young and well educated compared to the average tourists that visited Portugal. The results suggest that many tourists were aware of the city status as a world heritage site that encompasses a historic center, monuments, and architectural buildings. Furthermore, these perceptions shape the image of Guimara˜es, as the factor analysis indicates that ‘‘historical background and functionality’’ was the most reliable and valid factor behind the choice of visiting the city.